2018
DOI: 10.24083/apjhm.v11i1.243
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Pathology Collection in Australia

Abstract: Objectives: The specific objectives of the study were to (a) identify current best practice in pathology specimen collection and assess the extent to which Australian pathology services currently satisfy best practice standards; and (b) identify training and other strategies that would mitigate any gaps between current and best practice. Methods: A total of 22 case studies were undertaken with pathology collector employers from public, not for profit and private pathology organisations andacross urban an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
1
2
Order By: Relevance
“…No difference was found in the haemolysis rate related to the qualification of the blood collector with similar results found in haemolysis between medical, nursing and pathology staff. This contrasts with previous reports by Pilbeam et al, (2013) Similarly, a study by Abbas et al, (2017) found no difference in rejection rates for blood samples post-phlebotomy training for health workers. No studies were found that examined the education of staff regarding blood sampling from intravenous cannulas.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…No difference was found in the haemolysis rate related to the qualification of the blood collector with similar results found in haemolysis between medical, nursing and pathology staff. This contrasts with previous reports by Pilbeam et al, (2013) Similarly, a study by Abbas et al, (2017) found no difference in rejection rates for blood samples post-phlebotomy training for health workers. No studies were found that examined the education of staff regarding blood sampling from intravenous cannulas.…”
Section: Discussioncontrasting
confidence: 96%
“…, 6.8% in two emergency departments in university teaching hospitals. This contrasts with the 22.4% previously reported by Pilbeam et al, (2013) for emergency departments in Australia.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation